IMPLEMENTASI STUDI PSIKOLOGI BELAJAR SISWA - Zainur Arifin (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Learning is a means tarbiyah people, therefore, learning is a process of behavior change that comes from experience. Learning to not only remember but broader than that, the experience, not a mastery learning outcome results of the exercise but behavior change, learning activities can be lived (experienced) by a person who is learning and can also be observed by others. Psychology of children's learning is the process of guidance to learners' personal formation kerarah good Muslim (perfect man). the success of the students are not separated development of Learning child socio-emotional development of Learning Children In Identity, Development of Children Study In Consciousness Morality In Children, Biological Development and Perceptual Learning Child Physical Development Children Study Implications for Healthcare and Nutrition Children all of it as the assessment centers children's learning.